The anti‐C5a antibody vilobelimab efficiently inhibits C5a in patients with severe COVID‐19. Issue 4 (14th January 2022) - Vlaar, Alexander P. J.; Lim, Endry H. T.; de Bruin, Sanne; Rückinger, Simon; Pilz, Korinna; Brouwer, Matthijs C.; Guo, Ren‐Feng; Heunks, Leo M. A.; Busch, Matthias H.; van Paassen, Pieter; Riedemann, Niels C.; van de Beek, Diederik
Abstract: Recently, we reported the phase II portion of the adaptive phase II/III PANAMO trial exploring potential benefit and safety of selectively blocking C5a with the monoclonal antibody vilobelimab (IFX‐1) in patients with severe coronavirus disease 2019 (COVID‐19). The potent anaphylatoxin C5a attracts neutrophils and monocytes to the infection site, causes tissue damage by oxidative radical formation and enzyme releases, and leads to activation of the coagulation system. Results demonstrated that C5a inhibition with vilobelimab was safe and secondary outcomes appeared in favor of vilobelimab. We now report the pharmacokinetic/pharmacodynamic (PK/PD) analysis of the phase II study. Between March 31 and April 24, 2020, 30 patients with severe COVID‐19 pneumonia confirmed by real‐time polymerase chain reaction were randomly assigned 1:1 to receive vilobelimab plus best supportive care or best supportive care only. Samples for measurement of vilobelimab, C3a and C5a blood concentrations were taken. Vilobelimab predose (trough) drug concentrations in plasma ranged from 84, 846 to 248, 592 ng/ml (571 to 1674 nM) with a geometric mean of 151, 702 ng/ml (1022 nM) on day 2 and from 80, 060 to 200, 746 ng/ml (539 to 1352 nM) with a geometric mean of 139, 503 ng/ml (939 nM) on day 8. After the first vilobelimab infusion, C5a concentrations were suppressed in the vilobelimab group (median 39.70 ng/ml 4.8 nM, IQR 33.20–45.55) as compared to the control group (median 158.53 ng/ml 19.1 nM, IQR 60.03–200.89, p  = 0.0006). The suppression was maintained on day 8 ( p  = 0.001). The current PK/PD analysis shows that vilobelimab efficiently inhibits C5a in patients with severe COVID‐19.